Designing Multi-Dimensional User Interaction for a Virtual Museum System - Tengku Siti Meriam Tengku Wook; Noraidah Sahari @ Ashaari; Normala Rahim (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The focus of this study is to improve the display platform for the State of Terengganu Virtual Museum System (muziummaya.terengganu.gov.my). The existing virtual museum can be displayed via desktop computing system where information is displayed on-line using features for searching, browsing, and manipulating artifacts and galleries. However, presentation of information on mobile device screens cannot be viewed effectively and is difficult to navigate due to the user's cognitive load. Therefore, this study will establish effective interaction design, taking into account the multi-dimensional context for the design of a user interface via a mobile device in the hopes that users who are students, curators, researchers, and the public can access the virtual museum system via desktop as well as from their mobile devices. This study was conducted in three stages i.e. user requirements analysis, interface design, and usability evaluation. The results of this research is the design of a multi-dimensional user interaction context that meets the display requirements and navigation information for mobile devices.